Myoblast Myogenic Differentiation but Not Fusion Process Is Inhibited via MyoD Tetraplex Interaction. (7th May 2018) - Testa, Stefano; D'Addabbo, Pietro; Fornetti, Ersilia; Belli, Roberta; Fuoco, Claudia; Bernardini, Sergio; Cannata, Stefano; Frezza, Domenico; Gargioli, Cesare
Abstract : The presence of tetraplex structures in the promoter region of the myogenic differentiation 1 gene (MyoD1) was investigated with a specific tetraplex-binding porphyrin (TMPyP4), to test its influence on the expression of MyoD1 itself and downstream-regulated genes during myogenic differentiation. TMPyP4-exposed C2C12 myoblasts, blocking MyoD1 transcription, proliferated reaching confluence and fused forming elongated structures, resembling myotubes, devoid of myosin heavy chain 3 (MHC) expression. Besides lack of MHC, upon MyoD1 inhibition, other myogenic gene expressions were also affected in treated cells, while untreated control cell culture showed normal myotube formation expressing MyoD1, Myog, MRF4, Myf5, and MHC. Unexpectedly, the myomaker (Mymk) gene expression was not affected upon TMPyP4 exposure during C2C12 myogenic differentiation. At the genomic level, the bioinformatic comparison of putative tetraplex sites found that three tetraplexes in MyoD1 and Myog are highly conserved in mammals, while Mymk and MHC did not show any conserved tetraplexes in the analysed regions. Thus, here, we report for the first time that the inhibition of the MyoD1 promoter function, stabilizing the tetraplex region, affects downstream myogenic genes by blocking their expression, while leaving the expression of Mymk unaltered. These results reveal the existence of two distinct pathways: one leading to cell fusion and one guaranteeing correct myotube differentiation.